Biosorption of hazardous organic micropollutants to anaerobic sludge - 190550 Lokman Md. Hani; The Japan Society for the Promotion of Science; JSPS-VCC Seminar on Integrated Engineering (4th : 1992 : Kyoto, Japan)
10